Using Machine Learning and Natural Language Processing to Analyze Library Chat Reference Transcripts. - Yongming Wang (Information Technology & Libraries, 2022)
The use of artificial intelligence and machine learning has rapidly become a standard technology across all industries and businesses for gaining insight and predicting the future. In recent years, the library community has begun looking at ways to improve library services by applying AI and machine learning techniques to library data. Chat reference in libraries generates a large amount of data in the form of transcripts. This study uses machine learning and natural language processing methods to analyze one academic library's chat transcripts over a period of eight years. The built machine learning model tries to classify chat questions into a category of reference or nonreference questions. The purpose is to predict the category of future questions by the model with the hope that incoming questions can be channeled to appropriate library departments or staff.